Investigation of Turkish Children Perspective on Immigration Children: - (Third Sector Social Economic Review, 2026)
The purpose of this study is to reveal the perspectives of Turkish children attending pre-school education institutions toward their immigrant peers. In the research, children's emotions, thoughts, and behaviors regarding peers from different cultural backgrounds were examined within the context of social acceptance, empathy, communication, and friendship tendencies. The study employed the phenomenological design, one of the qualitative research methods. The study group consisted of 30 children aged 5–6 who attend independent kindergartens and have at least one immigrant child in their classroom. Data were collected through a five-question, illustrated semi-structured interview form developed by the researcher. The interviews were conducted individually by classroom teachers, and the children's responses were recorded verbatim. Phenomenological analysis technique was used for data analysis; children's expressions were coded, classified under themes, and supported by direct quotations. Research findings indicate that the vast majority of children exhibit positive, empathetic, and inclusive attitudes toward their immigrant peers. The children expressed a desire to play games, share the same desk, and become friends with their immigrant peers. However, some tendencies toward hesitation and prejudice were observed through expressions such as "I am afraid because I don’t know them" or "I don’t want to share my toys." Overall, the findings revealed that in children's perceptions of peers from different cultures, tendencies of empathy, curiosity, and social sharing are dominant, while themes of fear and insecurity are at a limited level.
Keywords: Preschool Education; immigrant children; social acceptance; empathy